Aplikasi Pupuk Anorganik dan Waktu Rendam Benih dengan Bakteri Legum pada Kacang Tanah di Lahan Pasang Surut - Billy Andreas Putra; Tengku Boumedine Hamid Zulkifli; Yunida Berliana; Octanina Sari Sijabat (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2020)
Introduction: The purpose of this study was to determine the dosage of inorganic fertilizers, soaking time of the inoculation of the legume bacteria strains which were suitable for the growth and yield of peanut in tidal lowland. Materials and Methods: This research was conducted at tidal lowland in Sei Ular Village, Secanggang sub-District, Langkat District, North Sumatra from September to December 2019. The research used randomized block design in factorial. The first factor is the dose of inorganic fertilizers consisting of P0 = un-fertilizer (control), P1= urea 50 kg.ha-1 + TSP 180 kg.ha-1 + KCl 50 kg.ha-1, P2= urea 75 kg.ha-1 + TSP 205 kg.ha-1 + KCl 75 kg.ha-1, P3= urea 100 kg.ha-1 + TSP 230 kg.ha-1 + KCl 100 kg.ha-1. The second factor was the soaking time of the Bradyrhizobium japonicum bacterial strain consisting of T0= un-soaking time, T1= soaking time for 3 minutes, T2= soaking time for 6 minutes, and T3= soaking time for 9 minutes. Parameters were analyzed using ANOVA and BNJ analysis 5%.· Results: The application of urea 50 kg.ha-1 + TSP 180 kg.ha-1 + KCl 50 kg.ha-1 significantly increased the plant height, number of leaves, and root volume and showed the highest number of active nodules, dry pods.plot-1 and seed weight.plot-1 compared to other doses. The seed soaking time with the Bradyrhizobium japonicum strain and their interactions showed insignificant differences in all parameters of peanut plants in tidal lowland.